The road to character [large type] - Brooks, David, 1961- (Thorndike Press, 2015)
"#1 New York Times bestselling author David Brooks, a controversial and eye-opening look at how our culture has lost sight of the value of humility - defined as the opposite of self-preoccupation - and why only an engaged inner life can yield true meaning and fulfillment"--